Policy recommendations for enhancing children's personal data protection: A case study in Vietnam - Dung, Thai Thi Tuyet; Duong, Nguyen Van (International Journal of Innovative Research and Scientific Studies, 2025)
In the digital age, protecting children's personal data is an urgent global problem, especially in Vietnam, where children use the internet at an alarming rate. Therefore, the objective of this study is to measure the impact of crucial elements on children's personal data protection in Vietnam using structural equation modeling (SEM). The authors made concrete policy proposals to help lawmakers improve children's personal data protection. The methodology employed a structural equation model based on data collected through qualitative interviews with ten legal experts specializing in child rights protection. These specialists provide professional perspectives on the current legal framework, policy enforcement issues, and prospective reforms. Additionally, the quantitative approach is based on a study of 450 respondents in Ho Chi Minh City, Vietnam. The findings of the study revealed that five important variables have a favorable impact on children's personal data protection: the legal system (LS), coordination among agencies (CA), awareness and training (AT), technology development (TD), and monitoring and violation handling (MV). Finally, the practical consequences presented policy recommendations to assist managers and legislators in establishing a personal data protection commission, harmonizing scattered legislation into a dedicated personal data protection act, and increasing penalties in line with global standards.